Hubungan Stres Kerja, Hubungan Interpersonal dan Tugas Tambahan dengan Beban Kerja Perawat di Ruangan Palma RSUP Prof. Dr. R. D. Kandou, Manado - Iramaya R. Sumayku; Alexander S. L. Bolang; Diana V. D. Doda; Welong S. Surya (e-CliniC, 2023)
Abstract: Covid-19 pandemic has had an impact on all aspects, especially on health care workers resulting in an increase in the physical workload of nurses. This study aimed to determine the relationship between work stress, interpersonal relationships, and additional tasks with the workload of nurses in Palma room of Prof. Dr. R. D. Kandou Hospital. This was a quantitative study. Samples were the total population of 48 nurses. Data were analyzed using the chi-square and the logistic regression tests. The results obtained sufficient and high workload (39.6% and 60.4%); sufficient and high work stress (31.3% and 68.8%); good and poor interpersonal relationship (47.9% and 52.1%); sufficient and high additional tasks (60.4% and 39.9%). The chi-square test showed the p-values, as follows: 0.001 for the relationship between work stress and workload; 0.000 for the relationship between interpersonal relationships and workload; and 0.034 for the relationship between additional tasks and workload. The logistic regression test found that the interpersonal relationship variable had the strongest relationship with workload compared to the other variables (Exp (B) interpersonal relationships, namely 11.441). In conclusion, there are relationships between work stress, interpersonal relationships, and additional tasks with the workload of nurses in Palma Room, Prof. Dr. R. D. Kandou Hospital, Manado. The most related variable with workload is interpersonal relationships. Keywords: workload; work stress; interpersonal relations; additional tasks   Abstrak: Pandemi Covid-19 membawa dampak pada semua aspek, terutama pada tenaga kesehatan perawat yang mengakibatkan meningkatnya beban kerja fisik perawat. Penelitian ini bertujuan untuk mengetahui hubungan antara stres kerja, hubungan interpersonal, dan tugas tambahan dengan beban kerja perawat di ruangan Palma RSUP Prof. Dr. R. D. Kandou. Jenis penelitian kuantitatif. Sampel ialah total populasi sebanyak 48 perawat. Analisis statistik menggunakan uji chi-square, dan regresi logistik. Hasil penelitian mendapatkan variabel beban kerja cukup dan tinggi (39,6% dan 60,4%); stres kerja cukup dan tinggi (31,3% dan 68,8%); hubungan interpersonal baik dan kurang baik (47,9% dan 52,1%); serta tugas tambahan cukup dan tinggi (60,4% dan 39,9%). Hasil uji chi square mendapatkan nilai p=0,001 untuk hubungan stres kerja dengan beban kerja; p=0,000 untuk hubungan interpersonal dengan beban kerja; p=0,034 untuk hubungan tugas tambahan dengan beban kerja. Hasil uji regresi logistik menunjukkan hubungan interpersonal memiliki hubungan paling kuat dengan beban kerja (Exp (B) hubungan interpersonal yaitu 11,441). Simpulan penelitian ini terdapat hubungan antara stres kerja, hubungan interpersonal, dan tugas tambahan dengan beban kerja perawat di Ruangan Palma RSUP Prof. Dr. R. D Kandou Manado dan variabel yang paling berhubungan dengan beban kerja ialah hubungan interpersonal. Kata kunci: beban kerja; stres kerja; hubungan interpersonal; tugas tambahan